INTERAKSI SOSIAL DAN MAKNA SIMBOLIS TRADISI MANTEN TEBU DI PABRIK GULA GEMPOLKEREP DALAM MEMBENTUK SINERGI SOSIAL - Adinda Dhea Rahmatia; Arief Sudrajat; Rizky Trisna Putri (Yayasan Literasi Sains Indonesia, 2025)
This study examines the Manten Tebu tradition at Gempolkerep Sugar Factory, Mojokerto, as a cultural expression and a medium for fostering social synergy that plays a vital role in sustaining sugar production and achieving national self-sufficiency. The research aims to understand the symbolic meanings of the ritual procession and analyze its role in strengthening the relationship between sugarcane farmers and the sugar factory. Employing a qualitative approach with a case study design, data were obtained through in-depth interviews, documentation, and participant observation, then analyzed using thematic analysis. Symbolic interactionism theory was applied to interpret how cultural meanings are constructed through social interaction. The findings reveal that elements such as the “bride and groom” sugarcane, ritual offerings, and the ceremonial parade carry collective symbols reflecting hopes for harmonious cooperation, shared prosperity, and abundant harvests. Collective participation, including communal meals without hierarchical divisions, reinforces social solidarity and emotional bonds. In conclusion, Manten Tebu is a living cultural asset that not only preserves local wisdom but also strengthens social networks, enhances work ethics, and promotes productivity in the sugar sector amid modernization challenges.